Analisis Nilai-Nilai Pendidikan Karakter dalam Novel Cold Couple Karya Bayu Permana dan Implementasinya dalam Pembelajaran - Hsb, Elysa Rohayani; Adam, Dini Hariyati (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Character education is the most important asset in human life to shape the character of students. The character values ​​in a literary work, a novel, can be used to shape students' characters. This research aims to analyze the values ​​of character education in the novel Cold Couple by Bayu Permana. This research was qualitative research using descriptive analysis methods. Data analysis techniques was carried out through data interpretation, reading all the data, analyzing it in more detail, applying a coding process to describe it, presenting it again in a narrative, and interpreting or interpreting the data. Data collection techniques using analysis unit determination techniques and data logging techniques. Data analysis techniques using content analysis techniques. The results of this research are the character education values ​​contained in the novel